1989
DOI: 10.1090/s0002-9939-1989-0946637-8
|View full text |Cite
|
Sign up to set email alerts
|

A proof of the Fefferman-Stein-Strömberg inequality for the sharp maximal functions

Abstract: Abstract.We give another proof of a theorem of Strömberg for the FeffermanStein sharp maximal functions. Our method is based on a decomposition lemma which is due to the arguments of Carleson, Garnett and Jones for the functions of BMO, and it is valid for a two-weight setting under a condition which is equivalent to the Aoo condition in the case of equal weights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Then Garnett and Jones [11] obtained a dyadic reformulation of Carleson's result with a different proof. Fujii [9] observed that almost the same proof as in [11] yields actually a decomposition of an arbitrary locally integrable function: given a cube Q, we have…”
Section: Motivation and Main Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Then Garnett and Jones [11] obtained a dyadic reformulation of Carleson's result with a different proof. Fujii [9] observed that almost the same proof as in [11] yields actually a decomposition of an arbitrary locally integrable function: given a cube Q, we have…”
Section: Motivation and Main Resultsmentioning
confidence: 77%
“…It was noted by Fujii [9] without the proof that replacing f Q in (1.4) by a median value m f (Q), one can obtain a similar decomposition but with the local sharp maximal function instead of f # Q (x). Indeed, certain modifications of the proof in [9] yield such a variant of (1.4) with a control of g by M # λ f and with (1.5) replaced by…”
Section: Motivation and Main Resultsmentioning
confidence: 99%
“…This lemma is based on several known ideas. The first idea is an estimate by oscillations over a sparse family (see [11,16,22]) and the second idea is an augmentation process (see Section 2.1).…”
Section: 3mentioning
confidence: 99%
“…We remark that the condition like (4) appears in [4]. We are mainly interested in the function f ∈ C p q (µ) such that M(f ) = 0.…”
Section: As a Results (3) Is Provedmentioning
confidence: 99%